PENERAPAN METODE VAKT (VISUAL, AUDITORY, KINESTHETIC, TACTILE) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 3 SD - Andriani, Yuli; Hendiawan, Deri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading proficiency is the fundamental cornerstone of the educational process, yet many third-grade students continue to face substantial hurdles in early literacy, often categorized as